2005
DOI: 10.1139/f05-142
|View full text |Cite
|
Sign up to set email alerts
|

Using tree-ring crossdating techniques to validate annual growth increments in long-lived fishes

Abstract: We applied crossdating, a dendrochronology (tree-ring analysis) age validation technique, to growth increment widths of 50 Sebastes diploproa otoliths ranging from 30 to 84 years in age. Synchronous growth patterns were matched by the following: (i) checking the dates of conspicuously narrow growth increments for agreement among samples and (ii) statistically verifying that growth patterns correlated among samples. To statistically verify pattern matching, we fit each time series of otolith measurements with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 19 publications
5
133
2
Order By: Relevance
“…Dorn (1992) also suggested that since euphausiids are the principal prey not only for splitnose rockfish and other Sebastes species, but also support numerous fish populations of the California Current System, it is unlikely that changes in the abundance of several Sebastes species alone could have had a substantial impact on the overall abundance of euphausiids. Environmental effects on splitnose rockfish growth were studied further by Black et al (2005) and Black (2009) using crossdating technique from dendrochronology. Crossdating is based on the assumptions that growth increment width in hard parts, like otoliths, is limited by some aspect of climate, and since the intensity of this climatic variable fluctuates over regular time intervals, climate induces covarying growth patterns in otolith increment widths much as it does in tree rings (Black et al 2005).…”
Section: Explaining Latitudinal Differences In Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorn (1992) also suggested that since euphausiids are the principal prey not only for splitnose rockfish and other Sebastes species, but also support numerous fish populations of the California Current System, it is unlikely that changes in the abundance of several Sebastes species alone could have had a substantial impact on the overall abundance of euphausiids. Environmental effects on splitnose rockfish growth were studied further by Black et al (2005) and Black (2009) using crossdating technique from dendrochronology. Crossdating is based on the assumptions that growth increment width in hard parts, like otoliths, is limited by some aspect of climate, and since the intensity of this climatic variable fluctuates over regular time intervals, climate induces covarying growth patterns in otolith increment widths much as it does in tree rings (Black et al 2005).…”
Section: Explaining Latitudinal Differences In Growth Parametersmentioning
confidence: 99%
“…Environmental effects on splitnose rockfish growth were studied further by Black et al (2005) and Black (2009) using crossdating technique from dendrochronology. Crossdating is based on the assumptions that growth increment width in hard parts, like otoliths, is limited by some aspect of climate, and since the intensity of this climatic variable fluctuates over regular time intervals, climate induces covarying growth patterns in otolith increment widths much as it does in tree rings (Black et al 2005). Black et al (2005) studied annual growth increments formed in splitnose rockfish otoliths collected between Point Conception and Cape Mendocino (Fig.…”
Section: Explaining Latitudinal Differences In Growth Parametersmentioning
confidence: 99%
“…Fish were collected by using a combination of hook-and-line sampling, trammel-netting, and spearfishing in shallow (<15 m) rocky reef habitats from 2009 to 2011. Otoliths were removed, sectioned, and mounted on slides to measure annual increment widths on high-resolution digital images that were captured with a digital camera (Leica DFC Model 425 or 450; 5-megapixel resolution) mounted on a stereomicroscope (Leica Model MZ6 or M60) under 20-40× magnification following the methods of Black et al (2005). These polishing and photographing procedures were sufficient to clearly reveal growth increment structure in most of the samples; only otoliths with clearly defined growth increment boundaries were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…These polishing and photographing procedures were sufficient to clearly reveal growth increment structure in most of the samples; only otoliths with clearly defined growth increment boundaries were used in the study. Dendrochronology crossdating procedures were used to verify that all increments were assigned the correct calendar year of formation (Black et al 2005) and to assess measurement error. If measurement error was high, visual crossdating and the statistical interseries correlation results from the software COFECHA (Grissino-Mayer 2001) were used to determine whether there was low synchrony among individuals, indicative of high error rates or weak environmental signals.…”
Section: Methodsmentioning
confidence: 99%
“…Black et al 2005;Tracey et al 2016). With regard to longevity, estimated ages of 35 (Bajer and Sorensen 2010) and 23 years (Brown et al 2003) have been reported for carp based on otolith sections, although the oldest (mark-recapture validated) age using this method has been up to 14 years ).…”
Section: Limited Longevitymentioning
confidence: 99%